La técnica del subrayado para mejorar la comprensión lectora de séptimo B, de la Unidad Educativa “José Ángel Palacio” de Loja, 2021-2022. - Jiménez Vega, Elsa Janeth (2022)
The current search is about the underlining technique to improve the reading comprehension of seventh grade, parallel B of "José Angel Palacio" high school, located in Loja city, academic year 2021–2022, which has as a general objective to determine the influence of the underlining technique to improve reading comprehension. This objective allowed us to pick up the most relevant information about the studied objective, so it is important that students develop the capacity to comprehend, understand, and synthesize the contents in the correct form as well as get the benefits of reading. According to theoretical framework, it helped us to analyze in the searching work the information about formulated variables in a systematic way; it allowed us to analyze the concepts that describe the main factors of the problem found with different bibliographic sources used and the contrast’s contributions. Moreover, the methodology permitted us to work through a group of procedures and techniques that consolidate this research work; in the same way, it worked with different methods that directed this case study. Referring to the instruments, we applied a questionnaire in order to pick up important information that supports the searching work elaboration. The investigated population was constituted by twenty-nine students and one teacher who helped us to appreciate the problem through a question bank related to the topic. Finally, it outlines the suggestions based on the results obtained in this investigation. Key words: Underlining technique, reading comprehension, Importance of underlining